Non-specific vascular skin lesions in the course of systemic lupus erythematosus - Hawro, Tomasz; Sysa-Jędrzejowska, Anna; Woźniacka, Anna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Lupus erythematosus skin lesions may be specific, with a characteristic microscopic pattern, or non-specific, without microscopic specificity. The vast majority of lupus non-specific skin lesions are vascular cutaneous changes: ulcerations, livedo reticularis, urticarial vasculitis, palpable purpura, ecchymoses, palmar and nailfold erythema and digital necrosis. Objective. To determine the prevalence of lupus non-specific skin lesions of vascular type and assess its correlations with other clinical features in a group of systemic lupus erythematosus patients. Material and methods. The examined group comprised 63 systemic lupus erythematosus patients. The diagnosis was established according to the American College of Rheumatology criteria. Mean patients’ age was 41 years, ranging from 20 to 67 years. Disease activity was assessed with the Systemic Lupus Activity Measure (SLAM). Results. Lupus non-specific skin lesions of vascular type were diagnosed in 77.78% of the examined group. Skin ulcers were present in 11.11%, livedo reticularis in 30.16%, urticarial vasculitis in 7.94%, thenar and hypothenar erythema in 58.73%, fingertips erythema in 52.38%, nailfold erythema in 33.33%, subungual splinter haemorrhage in 17.46%, ecchymoses on extremities in 30.16%, palpable purpura in 6.35% and digital necrosis in 9.5%. There was a significant (p < 0.05) correlation between disease activity and ulcerations, livedo reticularis, urticarial vasculitis, subungual splinter haemorrhages, ecchymoses on extremities and palpable purpura. Conclusions. The correlation between some lupus non-specific skin lesions of vascular origin and disease activity may indicate their prognostic value in the course of systemic lupus erythematosus.